Collective Actions and the Management of Collectively Provided Rangeland Resources and Activities in Awbere District of Somali Regional State, Ethiopia - Egge, Mahdi; Tongdeelert, Pichai; Rangsipaht, Savitree; Tudsri, Sayan (Kasetsart Journal of Social Sciences, 2011)
The main purpose of this research was to explore collective activities in rangeland management and utilization, and the management of collectively provided resources and activities. Key informant interviews and focus group discussions were conducted to collect data. In each of the ten Kebeles (villages), three to four focus group discussions were held with seven members in each group at a time. The collected data were analyzed through qualitative data analysis techniques such as narrative and ethnographic analyses. The results revealed that four kinds of collective actions with distinct rules for managing the collective activities existed in the Awbere district. These activities were: constructing ponds and water wells, collective herding, labor sharing for agricultural and social activities, and Diya paying groups. Each of these activities was conducted through the provision of labor and contributions depending on the type of operation, and noncontributors had restricted access to the water resources and benefits obtained from the collective activities. The results confirmed that community collective actions contribute to more sustainable use of the resource and social capital to improve community livelihoods. It was considered unlikely that rangeland resource problems could be solved by the community alone. Therefore, collective actions that improve rangeland resources need to be enforced with the support of development agencies, and development intervention strategies for managing rangeland resources need to be identified and introduced.